Social Return on Investment (SROI) of mental health related interventions—A scoping review - Kadel, Rajendra; Stielke, Anna; Ashton, Kathryn; Masters, Rebecca; Dyakova, Mariana (Frontiers in Public Health, 2022)
Background There is growing interest on how to effectively assess the benefits of mental health interventions in wider terms, capturing social, economic and environmental impacts. Social Return on Investment (SROI) is a methodological approach which incorporates all three aspects for evaluating such interventions. This study aims to map existing evidence on the social value of mental health interventions that uses the SROI methodology. Methods A scoping evidence search was conducted on Medline, PubMed, Google Scholar and relevant grey literature, published in English between January 2000 and March 2021 to identify studies which capture the social return on investment of mental health interventions in high- and middle-income countries. Studies that reported mental health outcomes and an SROI ratio were included in this review. The quality of included studies was assessed using Krlev’s 12-item quality assessment framework. Results The search identified a total of 435 records, and 42 of them with varying quality met the study inclusion criteria. Most of the included studies (93%) were non-peer reviewed publicly available reports, predominantly conducted in the United Kingdom (80%), and the majority (40%) were funded by local organisations. Out of 42 included studies, 22 were targeted towards individuals experiencing mental health problems and the remainder were targeted to vulnerable groups or the general population to prevent, or reduce the risk of poor mental health. Eighty-one percent of included studies were graded as high quality studies based on Krlev’s 12-item quality assessment framework. The reported SROI ratios of the included studies ranged from £0.79 (in a two year period) to £14.55 (in a year period) for every pound invested, with an exception of £28.00 for every pound invested (in a two year period). Conclusion This scoping review has found a good wealth of SROI studies that show a positive return on investment of the identified mental health interventions. This review illustrates how SROI could be a useful tool to inform policy decisions for investment in mental health and wellbeing, as this tool accounts for wider social, economic and environmental benefits of public health interventions.